2023
DOI: 10.1007/s11069-023-05912-3
|View full text |Cite
|
Sign up to set email alerts
|

An evaluation of the mine water inrush based on the deep learning of ISMOTE

Abstract: In order to establish an effective coal mine floor water inrush prediction model, a neural network prediction method of water inrush based on an improved SMOTE algorithm expanding a small sample dataset and optimizing a deep confidence network was proposed. ISMOTE is used to enlarge the coal mine's measured data collection, while PCA is used to minimize the data's dimension. DBN is used to extract water inrush data features and estimate water inrush danger in coal mines. As the water inrush samples are small, … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…In recent years, there has been a significant surge of interest in utilizing deep learning techniques to address complex challenges posed by collective effects. Numerous successful applications in geological disaster prediction, such as landslides (Zhang et al, 2019;Zhou et al, 2016), debris flow (Kern et al, 2017), and water inrush (Hu et al, 2013b;Dong et al, 2019;Shams et al, 2023;Ye et al, 2023), have demonstrated the efficacy of employing deep learning in scenarios involving similar mechanisms. To enhance the precision of evaluating oil-type gas emission disasters, a training model is proposed that combines Genetic Algorithm (GA) with Backpropagation (BP) neural network techniques (Zhu et al, 2023).…”
Section: Prediction Of Oil-type Gas Emission Quantitymentioning
confidence: 99%
“…In recent years, there has been a significant surge of interest in utilizing deep learning techniques to address complex challenges posed by collective effects. Numerous successful applications in geological disaster prediction, such as landslides (Zhang et al, 2019;Zhou et al, 2016), debris flow (Kern et al, 2017), and water inrush (Hu et al, 2013b;Dong et al, 2019;Shams et al, 2023;Ye et al, 2023), have demonstrated the efficacy of employing deep learning in scenarios involving similar mechanisms. To enhance the precision of evaluating oil-type gas emission disasters, a training model is proposed that combines Genetic Algorithm (GA) with Backpropagation (BP) neural network techniques (Zhu et al, 2023).…”
Section: Prediction Of Oil-type Gas Emission Quantitymentioning
confidence: 99%
“…Zhang et al developed an integrated floor water inrush model to predict the risk of water inrush caused by highly confined aquifers under complex stress conditions 11 . Ye et al proposed a neural network prediction method based on deep learning and used the improved synthetic minority oversampling technique (ISMOTE) to improve the accuracy of water inrush predictions 12 . Studies of the prediction and risk assessment theory for mine water hazards have led to a decreasing trend of water inrush accidents over time 13 .…”
Section: Introductionmentioning
confidence: 99%